Draft Annual Plan 1993-94 Union Territory Administration of Dadra and Nagar Haveli Silvassa - Planning Commission (Planning Commission, 1993)
Dadra and Nagar Haveli is an Union Territory without Legislature. The Governor of Goa is also the Administrator of this Territory. This is a single tier, State-cum- District-cum-Taluka Administration. The Administration is charged with the responsibility of performing almost all the functions being performed by States and other Union Territories such as formulation of policies, preparation of development Five Year and Annual Plans. This is being discharged by the new Secretariate set-up which started functioning recently.
Union Territory Administration of Dadra and Nagar Haveli Silvassa, Planning Division